2017
DOI: 10.1055/s-0037-1601879
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Orthopaedic Disease: Sarcoidosis—A Case Report

Abstract: Sarcoidosis is an idiopathic, noncaseating granulomatous disorder with wide systemic involvement. It is encountered widely around the world and it affects both sexes, all the races in all age groups. Lungs, eyes, and skin are the organs most commonly affected. Constitutional features such as weight loss, fatigue, and myalgia are the most common symptoms. Bone involvement, which is very rare, was reported as present in 3 to 13% of effected cases, and it is most commonly seen in hands and feet, compared with lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[6] CT scan of skull identifies sarcoid lesions as regions of enhanced uptake in subcutaneous area with areas of bone destruction and sclerosis. [7,8] MRI findings are high-intensity signals in T2weighted images. [8] However, in our patient, these imaging modalities were inconclusive and histopathology revealed the typical sarcoidal granulomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] CT scan of skull identifies sarcoid lesions as regions of enhanced uptake in subcutaneous area with areas of bone destruction and sclerosis. [7,8] MRI findings are high-intensity signals in T2weighted images. [8] However, in our patient, these imaging modalities were inconclusive and histopathology revealed the typical sarcoidal granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] MRI findings are high-intensity signals in T2weighted images. [8] However, in our patient, these imaging modalities were inconclusive and histopathology revealed the typical sarcoidal granulomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that bone cysts are more common in black people [24]. Various locations of sarcoidosis within the bone have different presentations, including apple core pattern in the finger [25], and different X-ray pictures in the long bones [26][27][28][29]. In some patients, bone lesions are described as having a "moth-eaten" pattern involving the cortex of the phalanges and accompanied by soft tissue swelling.…”
Section: Site Of Bone Involvementmentioning
confidence: 99%